Didactique de la grammaire en classe de FLE: état des lieux - Bendennoune, Jonathan; Adler, Silvia (Neofilolog, 2025)
The instruction of grammar within French as a Foreign Language (FFL) pedagogy raises critical questions regarding the intricate interplay between theoretical frameworks and methodological applications. This article undertakes an examination of the various potential “approaches” employed in the presentation of grammatical rules. Subsequently, it juxtaposes these approaches with our practical experience in teaching French within a university setting, with the aim of identifying any potential misconceptions or ambiguities that may have manifested in the linguistic output of our learners.